Impact of agricultural foreign aid on agricultural growth in sub-saharan Africa: A dynamic specification - Alabi, Reuben Adeolu (International Food Policy Research Institute, 2014)
This study investigates the impact of foreign agricultural aid on agricultural GDP and productivity in Sub-Saharan Africa (SSA). I rely on secondary data regarding foreign agricultural aid, agricultural GDP, and productivity indicators from 47 SSA countries spanning 2002-2010 and employ a Generalized Method of Moments (GMM) framework.